Left atrial remodeling, early repolarization pattern, and inflammatory cytokines in professional soccer players - Stumpf, Christian; Simon, Michael; Wilhelm, Martin; Zimmermann, Stefan; Rost, Christian; Achenbach, Stephan; Brem, Matthias H. (Journal of Cardiology, 2016)
OBJECTIVES: Although regular physical exercise clearly reduces cardiovascular morbidity risk, long-term endurance sports practice has been recognized as a risk factor for atrial fibrillation (AF). However, the mechanisms how endurance sports can lead to AF are not yet clear. The aim of our present study was to investigate the influence of long-term endurance training on vagal tone, atrial size, and inflammatory profile in professional elite soccer players. METHODS: A total of 25 professional major league soccer players (mean age 24±4 years) and 20 sedentary controls (mean age 26±3 years) were included in the study and consecutively examined. All subjects underwent a sports cardiology check-up with physical examination, electrocardiography, echocardiography, exercise testing on a bicycle ergometer, and laboratory analysis [standard laboratory and cytokine profile: interleukin (IL)-6, tumor necrosis factor (TNF)-α, IL-8, IL-10]. RESULTS: Athletes were divided into two groups according to presence or absence of an early repolarization (ER) pattern, defined as a ST-segment elevation at the J-point (STE) ≥0.1mm in 2 leads. Athletes with an ER pattern showed significantly lower heart rate and an increased E/e' ratio compared to athletes without an ER pattern. STE significantly correlated with E/e' ratio as well as with left atrial (LA) volume. The pro-inflammatory cytokines IL-6, IL-8, TNF-α as well as the anti-inflammatory cytokine IL-10 were significantly elevated in all soccer players. However, athletes with an ER pattern had significantly higher IL-6 plasma levels than athletes without ER pattern. Furthermore, athletes with "high" level IL-6 had significantly larger LA volumes than players with "low" level IL-6. CONCLUSIONS: Athletes with an ER pattern had significantly higher E/e' ratios, reflecting higher atrial filling pressures, higher LA volume, and higher IL-6 plasma levels. All these factors may contribute to atrial remodeling over time and thus increase the risk of AF in long-term endurance sports.
EVALuna2:33695